A Design Method of Hybrid MMC Full-bridge Submodule Proportion Applied to DC Traction Power Supply System for Urban Rail Transit - Yanna XI; Xiaotong LI; Ziming LI; Yingdong WEI; Xiaoqian LI; Fangmin WANG; Wei LI; Weirui LI (Zhongguo dianli)
The characteristic of urban rail DC traction power supply system is low voltage and large current. The capacity of a converter fails to meet the demand, limited by the current capacity of the switching device. Hybrid modular multilevel converter (MMC) is composed of full-bridge submodule and half-bridge submodule. It can be used in systems with modulation ratio greater than one. Utilizing the negative level output capability of the full-bridge submodule, the increase of the AC voltage or the reduction of the DC voltage can be achieved. This article is aimed at the hybrid MMC that can be applied in the DC traction power supply system and proposes a design method for the proportion of full-bridge submodule. This method meets the needs of high modulation ratio steady state operation and DC fault clearing capability. A 1 500 V subway system is selected as an example and three sets of parameters are also selected. The simulation model was built in PSCAD software to verify the correctness of the design method.